International journalism - Williams, Kevin 1955- (Sage, 2011)
"What is the future of the foreign correspondent -- is there one? Tracing the historical development of international reporting, Kevin Williams examines the organizational structures, occupational culture, and information environment in which it is practiced to explore the argument that foreign correspondence is becoming extinct in the globalized world. Mapping the institutional, political, economic, cultural, and historical context within which news is gathered across borders, this book reveals how foreign correspondents are adapting to new global and commercial realities in how they gather, adapt, and disseminate news. Lucid and engaging, the book expertly probes three global models of reporting -- Anglo-American, European, and the developing world -- to lay bare the forces of technology, commercial constraint, and globalization that are changing how journalism is practiced and understood. Essential reading for students of journalism, this is a timely and thought-provoking book for anyone who wishes to fully grasp the core issues of journalism and reporting in a global context"--P. [4] of pbk. cover.